Atomistic level study of Ce3Si2 oxidation as an accident tolerant nuclear fuel surrogate. (March 2020) - Harrison, R.W.; Worth, R.N.; Buckley, J.; Abram, T.
Highlights: Intermetallic silicide compounds being pursued for accident tolerant nuclear fuels programmes globally. Oxidation mechanisms in Ce-Si as a surrogate for U-Si system reported for first time using atomistic scale techniques. Material decomposes from micron sized grains, forming complex oxide nanostructure causing pulverisation of material. Passivation of nanoscale Si regions by CeO2 leads to the incomplete oxidation. Abstract: The oxidation mechanisms of Ce3 Si2 (as a surrogate for U3 Si2 accident tolerant nuclear fuel) have been studied to 750 °C in flowing air. Discrepancies between the terminal and theoretical mass gains for complete oxidation, similar to previous works on the U3 Si2 system are attributed to incomplete oxidation of Si, which forms amorphous SiO2 and regions of nano-crystalline free Si. Nano-grained (<5 nm) CeO2 also formed after oxidation leading to pulverisation, the resulting composition and nano-structure may have highly deleterious consequences for the fuel material under oxidative atompsheres, increasing the rate of oxidation, spallation and fission product release.